2022
DOI: 10.1155/2022/9354714
|View full text |Cite
|
Sign up to set email alerts
|

Application of Suctioning Ureteral Access Sheath during Flexible Ureteroscopy for Renal Stones Decreases the Risk of Postoperative Systemic Inflammatory Response Syndrome

Abstract: Purpose. To clarify the efficiency and outcomes of suctioning ureteral access sheath (UAS) during flexible ureteroscopic lithotripsy (fURL) for the management of renal stones. Methods. Between January 2017 and January 2019, a total of 444 patients with renal stones undergoing fURL were divided into suctioning UAS and nonsuctioning UAS groups. The outcomes of patients in both groups were compared using a matched-pair analysis (1 : 1 scenario). Furthermore, a directed acyclic graph (DAG) was drawn to guide the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Zhu's comparative study showed that patients undergoing FURS with SUAS had a mean operative time of 49.7 ± 16.3 min, which was significantly shorter than the 57.0 ± 14.0 min observed in the traditional UAS group (p < 0.001), indicating the efficiency of SUAS in reducing operative time [41]. However, Qian et al found no significant difference in operative times between SUAS and traditional UAS groups, with means of 72.9 min and 80.0 min, respectively (p = 0.121), demonstrating that the impact of SUAS on operative time may vary depending on other unreported factors [42]. Considering the variability in operative times across studies, the use of SUAS has been enhanced by integrating an intelligent pressure-control system (IPCS).…”
Section: Results Of Review Of Experimental Studies (Table 1)mentioning
confidence: 96%
See 1 more Smart Citation
“…Zhu's comparative study showed that patients undergoing FURS with SUAS had a mean operative time of 49.7 ± 16.3 min, which was significantly shorter than the 57.0 ± 14.0 min observed in the traditional UAS group (p < 0.001), indicating the efficiency of SUAS in reducing operative time [41]. However, Qian et al found no significant difference in operative times between SUAS and traditional UAS groups, with means of 72.9 min and 80.0 min, respectively (p = 0.121), demonstrating that the impact of SUAS on operative time may vary depending on other unreported factors [42]. Considering the variability in operative times across studies, the use of SUAS has been enhanced by integrating an intelligent pressure-control system (IPCS).…”
Section: Results Of Review Of Experimental Studies (Table 1)mentioning
confidence: 96%
“…Huang's prospective study found a slight reduction in operative time, although statistically insignificant (p = 0.235), in time with FANS compared to traditional UAS, averaging 37.7 versus 40.3 min, respectively [49]. Qian et al [42] fever: 3.70% vs. 14.8%; p = 0.030; SIRS: 1.23% vs. 12.3%;…”
Section: Results Of Review Of Experimental Studies (Table 1)mentioning
confidence: 98%
“…Notably, these effects were most pronounced when large-diameter UAS was used 28 . Recent studies have shown that suctioning UAS 29 and the novel flexible vacuum-assisted UAS 30 are better at maintaining low intrapelvic pressure and reducing the incidence of postoperative infectious complications.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, these effects were most pronounced when large-diameter UAS was used 28 . Recent studies have shown that suctioning UAS 29 and the novel flexible vacuum-assisted UAS 30 are better at maintaining low intrapelvic pressure and reducing the incidence of postoperative infectious complications. Previous studies have reported some independent risk factors related to postoperative infection complications of RIRS, such as the presence of urine nitrite 9 , positive UC 8,9 , large stone burden, and diabetes mellitus 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…After this round of full text screening, nineteen studies were included in the final review. Five of these nineteen studies [16,17,[19][20][21] were identified during the updated search in June 2022. References of the final nineteen studies were also screened for relevant studies.…”
Section: Characteristics Of the Final Studies Includedmentioning
confidence: 99%